Revolusi Kitab Undang-Undang Hukum Pidana terhadap Tantangan Konstitusionalitas dalam Kajian Siyasah Dusturiyah - Junmawalidin Junmawalidin (Lembaga Yasin AlSys, 2026)
The reform of the Criminal Code (KUHP) needs to consider the principle of justice for the people so that criminal regulation does not become an instrument serving the interests of officials who formulate the rules. This study aims to examine changes to the KUHP in relation to the challenges of constitutionality from the perspective of siyasah dusturiyah and to analyze them through the framework of Islamic legal politics. This study used a normative juridical method with conceptual and statutory approaches. The focus of the study was directed at material issues in the articles of the new National KUHP as regulated in Law Number 1 of 2023 and Law Number 1 of 2026 concerning Criminal Adjustment. The research data were analyzed descriptively and normatively by examining the conformity of the substance of criminal regulation with the principles of constitutionality, legal justice, and the values of Islamic legal politics. The results showed that the existence of the new KUHP of 2023 still leaves crucial issues, although it has been accompanied by criminal adjustment regulations in 2026. These issues relate to the need to ensure that criminal law reform remains oriented toward the interests of the people, is in line with the principle of constitutional justice, and does not create room for abuse of authority in the formation or application of law. These findings contribute to the development of studies on national criminal law and siyasah dusturiyah, particularly in assessing the direction of KUHP reform based on the principles of justice, public benefit, and protection of community rights. The implications of this study affirm the importance of strengthening normative evaluation of the substance of the KUHP so that national criminal law reform truly reflects substantive justice and the public interest.